Pengaruh Penambahan Bahan Alami Lateks (Getah Karet) Terhadap Karakteristik Beton Aspal Lapis Pengikat Dengan Pengujian Marshall - Suci Cahya Ferdilla; Gunawan Wibisono; Alfian Malik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In Indonesia, flexible pavements quite often occured prematurely. A good quality of pavement needs materials that fulfill a specification, and sometime also requires additional modifier. Rubber can be used to modify and increase of asphalt concretes quality. The addition of rubber is able to improve shear resistance at high temperatures, prevent cracks, bleeding, stripping, and permanent deformation of asphalt concretes. This study try to investigate the effect of natural rubber latex addition on a binder course typed asphalt concrete (AC-BC) based on volumetric properties of Bina Marga Specification Revision 3. The latex contents used as bitumen substitution were 0%, 4%, 6% and 8% of bitumen content. The results showed that the addition of rubber latexdecreased the optimum asphalt content and increased mixture densities. A maximum of 6% latex content could be used as bitumen substitution, where its Marshall characteristics still met the specification.Keyword : Rubber Latex, Laston AC-BC, Marshall characteristics, Specification ofBina Marga 2010 Revision 3.